Ulasan Kritis: Kemajuan Nanoformulasi Minyak Atsiri untuk Pengawetan Pangan - Syska, Kavadya (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2024)
Essential oils have great potential as antimicrobial and antioxidant agents for food preservation, but their effectiveness is influenced by factors such as concentration and interactions with food components. Nanoformulation design can improve the stability and bioavailability of essential oils, overcoming volatility and degradation issues, although challenges in emulsifier selection and production methods must be addressed. Mathematical modeling approaches allow the prediction of interactions in food systems, accelerating formulation development, but must be integrated with experimental data for validation. By improving stability, nanoformulations can potentially extend the shelf life of food products, reduce waste, and improve safety, although further research is needed to understand the long-term impacts and interactions with other food ingredients.